Design of Novel Yagi Aperture Antennas for Indoor TV Reception using Low Cost Materials - Sofian Hamid (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2012)
Most commercial Yagi antennas for TV reception are built based on wires. These Yagi wire-antennas are commonly used as outdoor antennas due to their size and weight properties. In this paper, novel light weight Yagi aperture antennas are introduced. Two prototypes had been built by using low cost materials such as aluminum (insects) screen, cylinder can, aluminum foil, and styrofoam. The antennas worked at the TV band and have gains around 9.7 – 13.5 dBi comparable to the outdoor Yagi wire antennas. Due to their lightweight and smaller dimension nature, they were suitable for used as indoor TV antennas. The antennas had also unique property due to the use of Styrofoam. They were portable, easy to construct and deconstruct.